(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Poisoning is one of the important causes of morbidity and mortality worldwide. The pattern of poisoning cases depends upon the availability of poisons and religious and cultural influence. The commonest cause in developing countries such as India is agrochemicals and household chemicals. More than 50,000 people die every year in India due to these poisonings. Knowledge about prevalent poisons in the region is much important in preventive these unfortunate deaths. Hence, this study was conducted to know the pattern of suicidal poisoning and the common poisons involved in the region of Faridabad. A retrospective study was carried out in the department of Forensic Medicine and Toxicology of ESIC Medical College, Faridabad in association with Badshah Khan Civil Hospital, Faridabad.During the present study a total of 82 suicidal poisoning cases were autopsied at Badshah Khan Hospital, Faridabad. Out of these cases, 48 cases were male and 34 cases were female. The commonest age group involved was 31-40 years followed by 21-30 years. The poison involved were aluminium phosphide, paraquat and methyl alcohol in males. In females the poison involved were aluminium phosphide and other pesticides. The most common reason was financial problems, family problems, relationship issue and chronic illness.